2019
DOI: 10.1021/acs.jpca.8b12313
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast X-ray Photoelectron Imaging of Attosecond Electron Dynamics in Molecular Coherent Excitation

Abstract: Ultrafast photoelectron imaging allows to measure information about coherent electron dynamic processes in materials or chemical compounds on femtosecond to attosecond time scales. We show that molecular time-resolved photoelectron diffraction produced by a time-delayed soft X-ray attosecond pulse can be used to monitor the ultrafast coherent excitation induced by a resonant UV pump pulse with variable carrierenvelope phases. Asymmetric diffraction angular patterns illustrate coherent electron dynamics of char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Such pulses allow one to take real-time snapshots of ultrafast transformations of matter [4]. Pumpprobe techniques using ultrashort sub-cycle laser pulses have made it possible to control the motion of electrons in atoms [5][6][7], molecules [8][9][10][11][12][13][14][15][16][17][18][19][20], and condensed phase systems [21] such as dielectrics, raising the fundamental question in this context about the relevance of the time scale of electronic coherences for chemical dynamics evolving on a much longer time scale: are electronic wavepackets created by ultrashort pulses relevant for the making and breaking of chemical bonds in a molecule?…”
Section: Introductionmentioning
confidence: 99%
“…Such pulses allow one to take real-time snapshots of ultrafast transformations of matter [4]. Pumpprobe techniques using ultrashort sub-cycle laser pulses have made it possible to control the motion of electrons in atoms [5][6][7], molecules [8][9][10][11][12][13][14][15][16][17][18][19][20], and condensed phase systems [21] such as dielectrics, raising the fundamental question in this context about the relevance of the time scale of electronic coherences for chemical dynamics evolving on a much longer time scale: are electronic wavepackets created by ultrashort pulses relevant for the making and breaking of chemical bonds in a molecule?…”
Section: Introductionmentioning
confidence: 99%
“…The question on how to properly image the electron dynamics in a molecule or atom in a nonstationary electronic state has been investigated in several theoretical works, specifically, in the context of x-ray scattering, [21][22][23][24][25][26] multidimensional spectroscopy, [27][28][29] transient x-ray absorption spectroscopy, 30 electron diffraction, 31 Auger electron spectroscopy, 32,33 and molecular-frame photoelectron spectroscopy. [34][35][36][37] All these studies have addressed electron wave-packet dynamics in the outervalence electron shells. Recent improvements of x-ray free-electron lasers have made it possible to create x-ray pulses with pulse durations below 1 fs, 38 which can be focused tightly to provide extremely high intensities sufficient for x-ray multiphoton ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Angular electronic fluxes can also be used to reconstruct electron charge migration in excited benzene by preparing a coherent electronic state [37,39], which can be monitored in photoelectron momentum spectra by a time-delayed high frequency attosecond pulses [43]. It is also found that molecular photoelectron angular distributions depend on the symmetry of molecular orbitals and molecular bondings, thus allowing to monitor electron coherent and charge migration [44][45][46][47]. Most recently, nonresonant ultrafast X-ray scattering from a molecular wave packet has been used to observe an adiabatic electron transfer in molecules [48].…”
Section: Introductionmentioning
confidence: 99%